GROWTH AND PRODUCTION OF THE Paspalum atratum GRASS GIVEN SOME DOSAGE OF FERTILIZER N, P, AND K ON VARIOUS HIGH DEFOLIATION - I W., Sugita; Duarsa, M.A.P.; Roni, N. G. K. (Jurnal Peternakan Tropika, 2019)
The study aimed to obtain information about the growth and production of Paspalum atratum grass given several doses of N, P, and K fertilizers at various high of defoliations. The research was carried out in the greenhouse of the Faculty of Animal science, Udayana University, Highway Sesetan  Merkisa, up to 11 weeks. The grass used was Paspalum atratum grass which was obtained at the research station from the Faculty of Animal science, Udayana University, Pangotan, Bangli. The design used was a completely randomized design (CRD) of spit plot patterns consisting of main plots, namely defoliation height 5 cm (D1), 10 cm (D2), 15 cm (D3) and 20 cm (D4), and subplot namely fertilizer dose (P0); without fertilizer, P1: 50 kg N ha-1 + 50 kg P 2 0 5 ha-1 + 50 kg K 2 O ha -1 (P2); 100 kg N ha -1 + 100 kg P 2 0 5 ha -1 + 100 kg K 2 O ha -1 (P3); 200 kg N ha -1 + 100 kg P 2 0 5 ha -1 + 100 kg K 2 O ha -1 . There were 16 combinations of treatments and repeated 3 times so that there were 48 experimental units. The variables observed were plant height, number of leaves, number of branches, chlorophyll content, root volume, leaf dry weight, root dry weight, stem dry weight, total forage dry weight, leaf  stem dry weight ratio, total forage / root ratio (top root ratio), and leaf area per pot. The results showed that high defoliation treatment had a significant effect (P <0.05) on shoot number, leaf dry weight, stem dry weight, total forage dry weight, leaf / stem dry weight ratio, total forage dry weight ratio, and leaf area per pot, while the treatment of N, P and K fertilizer dosages was significant (P <0.05) in all observed variables. The interaction between N, P and K fertilizer doses with high defoliation significantly affected root volume and dry / leaf weight ratio. Based on the results of the study it can be concluded that the highest growth and production of Paspalum atratum grass was produced on the treatment of P3 fertilizer dose (200 kg N ha -1 + 100 kg P 2 0 5 ha -1 + 100 kg K 2 O ha -1 ),  high Defoliation D4 (20 cm) and interaction between dose fertilizer with high defoliation at root volume and leaf / stem dry weight ratio. Keywords: Paspalum atratum, defoliation, N, P and K fertilizers